ANALISIS PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL, TERHADAP ETIKA AKUNTANSI - Helda Marlin Ala (Akademi Akuntansi YKPN Yogyakarta, 2018)
This study aims to analyze the influence of intelligence quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, the emotional quotient of spiritual quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, the influence of spiritual quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, and the influence of intelligence quotient, emotional quotient, and spiritual quotient simultaneosly on the accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang. The focus variables of research are intelligence quotient, spiritual quotient, spiritual quotient as independentvariables about accounting ethics as a bound variable.The results of this study can be seen that intelligence quotient and emotional quotient does significantly impact to accounting ethics, and spiritual quotient does significantly impact the accounting ethics. Keywords: Intelligence Quotient, Emotional Quotient, Spiritual Quotient, and Accounting Ethics.